The Effectiveness of Using Children's Songs in Developing Elementary Graders' English Vocabulary and Pronunciation in Jerusalem, Palestine / Iman I A Shehadeh and Mohammed A A Farrah - A Shehadeh, Iman I; A Farrah, Mohammed A (Universiti Teknologi MARA, Kedah, 2016)
This study aimed at investigating the effect of using children's songs in developing the elementary graders' vocabulary and pronunciation. It aimed also to investigate teachers' attitudes towards the use of songs in their English classes. The participants were 123 EFL students of the fourth grade; 72 females and 51 males. Arabic is their native language. Both groups are from four private schools in Jerusalem; two groups for boys, and two groups for girls. One boys’ school and one girls’ school were chosen to be the experimental group consisting of 58 participants, while the other boys’ and girls’ schools were chosen to be the control group consisting of 65 participants. Study data were collected via students' pre and post tests and teachers' questionnaire. Exams results showed that students have improved their vocabulary and pronunciation due to the use of songs in learning. Questionnaire results showed that teachers have positive attitudes towards the use of songs in their classes as songs have positive effects in increasing students' achievement, interest and motivation. Finally, results revealed that students' achievements were not affected by gender.